Governance and organisational structure in the special tourism sector – buyer-driven or producer-driven value chains? The case of trekking tourism in the Moroccan mountains - Lessmeister, Ralph (ERDKUNDE, 2008)
In the debate about economic globalisation, governance has become a central element. Especially studies working with a value chain concept emphasise the ability to direct and to control different economic actors at different geographical places in a globally-linked production process as a key competency for market success. But most of these studies focus on the industrial or agricultural sector. The value chain discussion drew only little attention to the phenomenon of international tourism, although it is one of the most important economic branches worldwide. And in tourism too, we find globally-linked value chains. So the question arises, of how far experiences and findings made within the various value chain studies undertaken so far may help us to gain insight into the governance structures and organisational patterns in the international tourism business. This article deals with the situation of the Moroccan mountain tourism as one example of internationally linked tourism. Based on the Global Commodity Chain concept by Gary Gereffi, it describes the different types of organisation and governance in this tourism chain and argues that the Commodity Chain concept represents a useful starting point for the analysis of tourism. However, because of the particularities in tourism, it is not able to explain all the existing forms of business relations. Referring to transaction cost theory it will seek to fill this gap and therefore contribute to a general understanding about how value chains in tourism are organised and governed. Finally, it will explain not only why, but also when different types of governance and organisation do prevail by integrating them into a life cycle model of tourism destinations.